THE SPIRITUAL AND EDUCATIONAL SIGNIFICANCE OF MODERATION AND PROPER EATING IN ISLAM - Allambergenova Jasmina; Eldor Shodiqulov (The Conference Hub, 2025)
This article analyzes the spiritual and hygienic importance of proper eating, moderation, and thorough chewing in Islamic teachings. Based on religious sources, hadiths, and modern medical research, it explains the physiological, psychological, and spiritual benefits of eating less. The article scientifically discusses the harmful consequences of overeating—such as cardiovascular, hepatic, and digestive system disorders. Furthermore, it highlights how improper nutrition affects mental balance and willpower, and explores the bioenergetic value of chewing. In Islam, eating in moderation is considered not only a guarantee of physical health but also a means of spiritual purification, patience, and intellectual cultivation. The paper emphasizes the relevance of Islamic medical-ethical principles in ensuring harmony between the body and the soul.
Keywords: Islamic teachings, proper nutrition, moderation in eating, eating etiquette, chewing culture, bioenergetics, digestive system, occupational hygiene, mental stability, healthy lifestyle, Ibn Sina, Qur’an, hadith.